2009
DOI: 10.1596/1813-9450-4913
|View full text |Cite
|
Sign up to set email alerts
|

Paying The Price For Unreliable Power Supplies: In-House Generation Of Electricity By Firms In Africa

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 12 publications
1
68
1
2
Order By: Relevance
“…Conversely, other studies have shown that intermittent, unreliable electricity, and unexpected outages or surges can hurt firm performance. Power outages cost businesses in terms of lost sales (e.g., Allcott, Collard-Wexler, and O'Connell, 2015;Beenstock, Goldin, and Haitovsky, 1997;Adenikinju, 2005) as well as equipment damage, as documented by Foster and Steinbuks (2009). Alam (2013) provided evidence of heterogeneity in the effect of outages, showing that power outages lower profits and output of some electricity-intensive industries in India, but not across the board.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Conversely, other studies have shown that intermittent, unreliable electricity, and unexpected outages or surges can hurt firm performance. Power outages cost businesses in terms of lost sales (e.g., Allcott, Collard-Wexler, and O'Connell, 2015;Beenstock, Goldin, and Haitovsky, 1997;Adenikinju, 2005) as well as equipment damage, as documented by Foster and Steinbuks (2009). Alam (2013) provided evidence of heterogeneity in the effect of outages, showing that power outages lower profits and output of some electricity-intensive industries in India, but not across the board.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Closest to our paper are contributions by Reinikka and Svensson (2002) and, more recently, by Foster andSteinbucks (2009) andSteinbucks (2008). Reinikka and Svensson analyze a sample of 171 Ugandan firms, some of which responded to poor electricity supply by investing in generators.…”
Section: Introductionmentioning
confidence: 69%
“…Since electricity is an essential input in production, it is thus natural that about 35% of plants in Indian manufacturing insure themselves against outages by self-generating or otherwise substituting away from grid electricity (Alcott et al, 2014;World Bank, 2013). The situation is similar in other developing countries where unreliable energy supply forces firms to invest in selfgeneration capacity at the expense of more productive capital, outsource part of the production process, or expand firm size (e.g., Alam, 2013;Alby et al, 2013;Fisher-Vanden et al, 2013;Foster and Steinbuks, 2009;Reinikka and Svensson, 2002;Zuberi, 2012).…”
mentioning
confidence: 90%